QTL Mapping for Hull Thickness and Related Traits in Hybrid Rice Xieyou 9308 - LUO, Li-li; ZHANG, Ying-xin; CHEN, Dai-bo; ZHAN, Xiao-deng; SHEN, Xi-hong; CHENG, Shi-hua; CAO, Li-yong (Rice science, 2014)
We conducted a quantitative trait locus （QTL） analysis of 165 rice recombinant inbred lines derived from a cross between Zhonghui 9308 （Z9308） and Xieqingzao B （XB） in Hainan and Hangzhou, China. Grain thickness （GT）, brown rice thickness （BRT）, hull thickness （HT） and milling quality were used for QTL mapping. HT was significantly and positively correlated with GT and BRT. Twenty-nine QTLs were detected with phenotypic effects ranging from 2.80% to 21.27%. Six QTLs, qGT3, qBRT3, qBRT4, qHT6.1, qHT8 and qHT11, were detected repeatedly across two environments. Inherited from XB qHT6.1, qHT8 and qHT11 showed stable expression, explaining 9.92%, 21.27% and 10.83% of the phenotypic variances in Hainan and 9.61%, 6.40% and 6.71% in Hangzhou, respectively. Additionally, the QTL cluster between RM5944 and RM5626 on chromosome 3 was probably responsible for GT and milling quality. The cluster between RM6992 and RM6473 on chromosome 4 played an important role in grain filling. Three near isogenic lines （NILs）, X345, X338 and X389, were selected because they contained homozygous fragments from Zhonghui 9308, corresponding to qHT6.1, qHT8 and qHT11, respectively. The hull of XB was thicker than those of X345, X338 and X389. In all the lines, qHT6.1, qHT8 and qHT11 that regulated rice HT were stably inherited with obvious genetic effects.